2020
DOI: 10.3390/antiox9050378
|View full text |Cite
|
Sign up to set email alerts
|

Citrus sinensis and Vitis vinifera Protect Cardiomyocytes from Doxorubicin-Induced Oxidative Stress: Evaluation of Onconutraceutical Potential of Vegetable Smoothies

Abstract: The interest towards nutraceuticals able to counteract drug side effects is continuously growing in current chemotherapeutic protocols. In the present study, we demonstrated that smoothies containing mixtures of Citrus sinensis and Vitis vinifera L. cv. Aglianico N, two typical fruits of the Mediterranean diet, possess bioactive polyphenols that protect cardiomyocytes against doxorubicin-induced oxidative stress. The polyphenolic extracts isolated from Citrus sinensis- and Vitis vinifera-based functional smoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The percentage of hypodiploid nuclei was analyzed using propidium iodide (PI) staining by flow cytometry [ 38 ]. Briefly, HaCaT cells (8.0 × 10 3 cells/well) were grown in 24-well plates and allowed to adhere.…”
Section: Methodsmentioning
confidence: 99%
“…The percentage of hypodiploid nuclei was analyzed using propidium iodide (PI) staining by flow cytometry [ 38 ]. Briefly, HaCaT cells (8.0 × 10 3 cells/well) were grown in 24-well plates and allowed to adhere.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies indicate that HPLC is the method of choice due to its precision and sensitivity for the determination and quantification of natural as well as synthetic antioxidants in various food/food products [45][46][47][59][60][61][62][63][64]. The main group of antioxidants investigated were phenolic compounds, especially phenolic acids, catechins, and flavonoids.…”
Section: Column Liqiud Chromatography In Analysis Of Selected Bioactive Compounds In Food Samplesmentioning
confidence: 99%
“…It has been widely claimed that when food ingredients are mixed rather than using a single material, the synergistic therapeutic effects due to the combination of biochemicals may be superior to that of single biochemicals [ 20 , 21 ]. Much research has reported that when the mixed material is treated, a more effective bioactive effect is exhibited than when a single material is treated [ 22 , 23 , 24 ]. In this study, we aimed to establish a mixing ratio that dramatically enhanced immune function by utilizing two natural resources of Jeju, FES and SQN.…”
Section: Introductionmentioning
confidence: 99%